The Influence of CYP7A1 and CYP1A2 Genes on the Pathogenesis of Pediatric Immune Thrombocytopenia Purpura - Rifaat Ali, Ammar; Ibrahim Maleek, Muthana (Journal of Neonatal Surgery, 2025)
Background: Immune thrombocytopenia (ITP) in pediatric patients is an autoimmune condition Illness characterized by persistent thrombocytopenia resulting from immune-mediated platelet depletion. The actual pathophysiology of ITP remains unclear, with hereditary variables likely impacting illness severity and development. Objective: The aim of the study is to evaluate the gene expression of the CYP7A1 and CYP1A2 genes in patients with ITP in comparison to healthy controls, and to examine their potential significance as diagnostic biomarkers for the illness. Methods: One hundred samples (fifty ITP cases and fifty controls) were analyzed from Wasit Oncology Center. Gene expression analysis of CYP7A1 and CYP1A2 was conducted via quantitative real-time polymerase chain reaction (qRT-PCR), normalized against GAPDH. The relative expression levels were evaluated with the Livak technique (2^-ΔΔCT), and a ROC analysis (receiver operating characteristic) was performed to determine its detection efficacy. Results: The gene expression levels of CYP7A1 and CYP1A2 were significantly higher in ITP patients compared to healthy controls (P < 0.001).ROC analysis found that CYP7A1 (AUC = 1.000, cutoff = 9.13) and CYP1A2 (AUC = 1.000, cutoff = 17.72) demonstrated 100% sensitivity and specificity. Conclusion: This study demonstrated a highly significant association between genes (CYP7A1 and CYP1A2) expression levels in ITP patients. This may indicate the role of genes in regulatory interaction in ITP pathogenesis